POPULATIONAL STUDY OF CHROMOSOME POLYMORPHISM IN ZONOTRICHIA-CAPENSIS (EMBERIZIDAE, PASSERIFORMES, AVES) - Desouza, E. B.; Delucca, E. J. (Soc Brasil Genetica, 1991)
The karyotypes of 328 specimens of Zonotrichia capensis from four regions, three in the state of Parana and one in the state of São Paulo (Brazil), were studied. This species presents a chromosomal polymorphism due to pericentric inversion, involving the 3rd and 5th chromosome pairs. Chromosome 3 exists in the 3st and 3sm conditions and chromosome 5, in 5st and 5m conditions. Mitotic metaphase spreads were obtained from bone-marrow material of colchicine-treated animals.At all collection sites the frequency of chromosome 5m was considerably lower than that of the inverted chromosome 3sm.The present work tried to establish a correlation between the frequencies of the 3rd and 5th chromosome pairs with the climatical and geographical parameters at the collecting regions.Data show that the frequency of chromosome 5m is higher in regions with low temperature and high altitude.